HISTORY OF THE DISCOVERY OF RADIOACTIVITY AND X-RAYS, NUCLEAR EXPLOSIONS EXPLANATION OF THE PHENOMENON RESEARCH USING INTERACTIVE METHODS - Elmurotova Dilnoza Baxtiyorovna; Fayziyeva Nodira Alisherovna; Bozorov Erkin Hozhievich (Web of Journals Publishing, 2025)
The work provides detailed explanations of the history of the discovery of radioactivity and X-rays, ways to study the phenomenon of nuclear explosions using interactive methods, and its scientific novelty is that in order to form students' competencies in teaching the topic, the "Brainstorming" method was used to determine the results of the organized training session. The results showed that the method increased students' interest in the lesson and strengthened their memory.
Keywords: Radioactivity, X-rays, nuclear explosion, interactive method, scientific innovation, student, competency, training session, empirical research, brainstorming, stage.